ANALISIS KELAYAKAN FINANSIAL BUDIDAYA TANAMAN KARET (Hevea brasiliensis) SKALA RAKYAT DI KAMPUNG TERING SEBERANG KECAMATAN TERING KABUPATEN KUTAI BARAT - Yohanis Pakalla Marampa’ dan Maskan AF (Agrifor : Jurnal Ilmu Pertanian dan Kehutanan, 2014)
Financial Feasibility Analysis of Small Scale Rubber Farming (Hevea brasiliensis) in Tering Seberang village, Tering Sub Disrict of West Kutai Regency.  This resarch was implemented from February to April 2013 and its objective was to count production cost, rubber farm income, and to assess rubber farm feasibility, as well as to indentify problems faced and its alternative solutions. The research was data were compiled with purposive sampling method at 20% precision level where from the total 20 respondents, 5 of them were taken to represent their group. The data were collected through questionnaire, interiew, literature review, and field observation, then they were classified and tabulated based on production cost and farm income, as well as their financial analysis. Results of the research revealed that the small scale rubber farming management Tering Seberang Village, Tering Sub District of west Kutai District had Net Present Value (NPV) > 0, it was Rp. 31.393.740 at 18% interset rate; Net Benefit Cost ( B/C ratio > 1 it was 4,84 at 18% interset rate; Gross B/C Ratio > 1, it was 2.04 at 18% interset rate; Internal Rate of Return (IRR) 16.8% at the year six or 28.8% at the year seven; and Payback Period (18%) was at 6 years 2 months 16 days.